Analysis of The Application of Logistics Management and Logistics Information Systems in The Quality of Goods Distribution Services on Customer Satisfaction - Jocelin Anwar, Akmal (Siber Journal of Transportation and Logistics, 2024)
The Influence of Logistics Management Implementation, Logistics Information Systems, and Quality of Goods Distribution Services on Customer Satisfaction is a scientific literature review article within the scope of the field of study. The purpose of this article is to develop hypotheses on the influence of independent variables on the dependent variable that will be used in subsequent research. The research objects are online media literature, Google Scholar, Semantic Scholar, Elsevier, Zotero, and other online journal media. The research method employs library research sourced from e-books and scientific journals. The analysis uses a qualitative descriptive approach. The results of this article show: 1) The Implementation of Logistics Management influences Customer Satisfaction; 2) Logistics Information Systems influence Customer Satisfaction; and 3) The Quality of Goods Distribution Services influences Customer Satisfaction.